Tears to triumph : the spiritual journey from suffering to enlightenment - Williamson, Marianne, 1952- (HarperOne, 2016)
The internationally recognized teacher, speaker, and New York Times bestselling author of A Return to Love argues that our desire to avoid pain is actually detrimental to our lives, disconnecting us from our deepest emotions and preventing true healing and spiritual transcendence. Marianne Williamson is a bestselling author, world-renowned teacher, and one of the most important spiritual voices of our time. In Tears to Triumph, she argues that we--as a culture and as individuals--have learned to avoid facing pain. By doing so, we are neglecting the spiritual work of healing,"--Amazon.com.